2022
DOI: 10.1177/02692163221113163
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder perspectives of a pilot multicomponent delirium prevention intervention for adult patients with advanced cancer in palliative care units: A behaviour change theory-based qualitative study

Abstract: Background: Theory-based and qualitative evaluations in pilot trials of complex clinical interventions help to understand quantitative results, as well as inform the feasibility and design of subsequent effectiveness and implementation trials. Aim: To explore patient, family, clinician and volunteer (‘stakeholder’) perspectives of the feasibility and acceptability of a multicomponent non-pharmacological delirium prevention intervention for adult patients with advanced cancer in four Australian palliative care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“… 8 , 9 A pilot study, reporting low adherence to a delirium prevention intervention, found that clinicians were more strongly motivated to enact responsive care than anticipatory. 44 Our theoretically informed analysis of the influences on this ‘reactive approach’ can be used to inform further research to develop effective interventions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 8 , 9 A pilot study, reporting low adherence to a delirium prevention intervention, found that clinicians were more strongly motivated to enact responsive care than anticipatory. 44 Our theoretically informed analysis of the influences on this ‘reactive approach’ can be used to inform further research to develop effective interventions.…”
Section: Discussionmentioning
confidence: 99%
“…A previous systematic review recommended inter-professional education for complex delirium care. 44 There is a need to develop a shared team understanding to enable a structured approach to delirium care; reflected by recent calls for effective and strong interdisciplinary collaboration in this field. 45 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Knowledge sharing within teams, incorporation of screening documentation into workflow and a culture of compassionate and collaborative working is important. 15,16 It is therefore as vital to find strategies to implement guideline-adherent care as it is to identify the optimal way to assess, manage and prevent delirium through clinical interventions. The Detection, Assessment, Management and Prevention of Delirium in Hospices (DAMPen-D) study 17 addresses this current gap.…”
Section: Introductionmentioning
confidence: 99%
“… 14 Knowledge sharing within teams, incorporation of screening documentation into workflow and a culture of compassionate and collaborative working is important. 15 , 16 …”
Section: Introductionmentioning
confidence: 99%